The economic relations between Latin America and China: a systemic perspective - Ouriques, Helton Ricardo (Universidade Estadual Paulista / UNESP, 2016)
This article intends to discuss the economic relations between China and Latin America in the Twenty-First Century, based on informations and statistical data that clear the arising of the chinese presence on Latin American countries. It also provides a systemic contribution to this subject, beyond the existing debate about risks and possibilities of this economic relation to the countries of the region.